2018
DOI: 10.1038/s41598-018-19990-y
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol–induced catalepsy is ameliorated by deep brain stimulation of the inferior colliculus

Abstract: Deep brain stimulation (DBS) has evolved as a promising alternative treatment for Parkinson’s disease (PD), but the underlying mechanisms remain poorly understood. Moreover, conventional DBS protocols targeted at basal ganglia sites can turn out completely ineffective for some PD patients, warranting the search for alternative targets. The inferior colliculus (IC) is a midbrain auditory relay station involved in sensorimotor processes. High-frequency 2500 Hz electrical stimulation of the IC elicits escape beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…Upon its release on public repositories of neuroimaging data and tools, this atlas might be used as a tool to better identify the IC, SC, MG, LG, SOC nuclei location in conventional (e.g., 3 Tesla) MRI, and enable more accurate characterizations of auditory and visual connectivity pathways in fMRI and diffusion tractography studies. The current work provides a detailed description of the location, shape and anatomy of these nuclei that could be useful in research as well as in future clinical studies to aid treatment delivery and tuning of strategies such as repetitive transcranial magnetic stimulation, neurosurgical planning or focused ultrasound therapies i.e., in tinnitus treatment (Smit et al, 2016; Yilmaz and Yilmaz, 2018) or advanced stages of Parkinson’s disease with catalepsy symptoms (Engelhardt et al, 2018). This atlas could also be used to evaluate microstructural changes in the brainstem, such as the location of microbleeds/lesions/tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Upon its release on public repositories of neuroimaging data and tools, this atlas might be used as a tool to better identify the IC, SC, MG, LG, SOC nuclei location in conventional (e.g., 3 Tesla) MRI, and enable more accurate characterizations of auditory and visual connectivity pathways in fMRI and diffusion tractography studies. The current work provides a detailed description of the location, shape and anatomy of these nuclei that could be useful in research as well as in future clinical studies to aid treatment delivery and tuning of strategies such as repetitive transcranial magnetic stimulation, neurosurgical planning or focused ultrasound therapies i.e., in tinnitus treatment (Smit et al, 2016; Yilmaz and Yilmaz, 2018) or advanced stages of Parkinson’s disease with catalepsy symptoms (Engelhardt et al, 2018). This atlas could also be used to evaluate microstructural changes in the brainstem, such as the location of microbleeds/lesions/tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that high-frequency DBS in the inferior colliculus (IC), a midbrain structure classically related to auditory processing, can serve as an alternative DBS target to ameliorate motor deficits in akinetic rats [ 9 , 10 ]. The IC is an important relay station for ascending and descending auditory information but is distinguished from other brainstem auditory nuclei by its indirect projections to motor pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 Tenkilohertz stimulation is effective for spinal cord stimulation for chronic leg and back pain, 22 and sub-50 Hz stimulation can be effective for stroke recovery, 15,16 chronic pain, 23 and catalepsy. 24 Certain parameters improve some symptoms while worsening others; high-frequency stimulation for primary parkinsonism symptoms exacerbates vocalization deficits. 25,26 We hypothesized that low-frequency stimulation would be most effective for ataxia because low-frequency stimulation enhances network throughput, 16,27 whereas high-frequency stimulation functions as an informational lesion.…”
mentioning
confidence: 99%
“…Parkinsonian DBS is usually >100 Hz, although 60 Hz can effectively treat bradykinesia . Ten‐kilohertz stimulation is effective for spinal cord stimulation for chronic leg and back pain, and sub‐50 Hz stimulation can be effective for stroke recovery, chronic pain, and catalepsy . Certain parameters improve some symptoms while worsening others; high‐frequency stimulation for primary parkinsonism symptoms exacerbates vocalization deficits .…”
mentioning
confidence: 99%